2021
DOI: 10.18393/ejss.807762
|View full text |Cite
|
Sign up to set email alerts
|

Vermicomposting of anaerobically digested sewage sludge with hazelnut husk and cow manure by earthworm Eisenia foetida

Abstract: Article InfoVermicomposting of organic waste has an important part to play in an integrated waste management strategy. The aim of the present study was to investigate the ability of an epigeic earthworm Eisenia foetida to transform anaerobically digested sewage sludge (SS) amended with hazelnut husk (HH) and cow manure (CM) in different proportions under laboratory condition (in darkness at 25°C0,5 0 C). Two approaches investigated in the study were: (1) to find the best medium for growth and reproduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This method offers an alternative to traditional composting techniques for recycling organic material. During vermicomposting, organic materials are rapidly humified, detoxified, and disinfected, aided by beneficial microorganisms and earthworms (Kızılkaya and Hepşen, 2014;Rakıcıoğlu and Kızılkaya, 2021). The epigeic earthworm species, Eisenia foetida 103 Vermicompost is a finely divided, peat-like substance with a low C: N ratio, superior structure, porosity, aeration, drainage, and water-holding capacity (Demir, 2019;2020;Yılmaz and Uğur, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This method offers an alternative to traditional composting techniques for recycling organic material. During vermicomposting, organic materials are rapidly humified, detoxified, and disinfected, aided by beneficial microorganisms and earthworms (Kızılkaya and Hepşen, 2014;Rakıcıoğlu and Kızılkaya, 2021). The epigeic earthworm species, Eisenia foetida 103 Vermicompost is a finely divided, peat-like substance with a low C: N ratio, superior structure, porosity, aeration, drainage, and water-holding capacity (Demir, 2019;2020;Yılmaz and Uğur, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, with the development of industrialization and urbanization, the yield of sewage sludge (SS) in Kazakhstan sharply increases every year (Ospanov et al, 2022). SS is a by product of waste water treatment process, which contains lots of organic matter, plant nutrients (N, P, K, Ca, Mg, etc) and harmful components such as potential toxic heavy metals and pathogenic microorganisms (Delibacak et al, 2020;Kızılkaya et al, 2021). The use of SS in agriculture includes several operations that improve its efficiency in crop production, as compared to mineral fertilizers, which are related to the stabilising process before spreading (Shashoug et al, 2017;Jatav et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Goss et al (2013) are of the same opinion. Several studies have been done related to organic amendments on improving soil physical, chemical, and biological properties, providing essential plant nutrients to stimulate plant growth and yield Hepşen, 2004, 2007;Candemir and Gülser, 2010;Gülser et al, 2017;Kızılkaya et al, 2021). Rodriguez-Vila et al (2016) found that organic amendments sustain soil properties by increasing organic matter, nutrient content, microbial activity and thus increase crop growth and yield.…”
Section: Introductionmentioning
confidence: 99%